Seawater quality and diversity of phytoplankton species in the waters of the North Coast of Jakarta - Moh. Hamdani; Khoe Susanto Kusumahadi; Tatang Mitra Setia (Indonesian Journal of Applied Environmental Studies, 2022)
The North Coast of Jakarta is a strategic area to support the economy of the DKI Jakarta Province and as a place to live for organisms, one of which is phytoplankton. Phytoplankton is a primary producer in aquatic ecosystems that have an essential role in maintaining aquatic ecosystems and as an indicator of water quality. This study aims to determine the quality of seawater (turbidity, TSS, BOD, Phosphate, and Nitrate) and the diversity of species (H') of phytoplankton in the waters of the North Coast of Jakarta around the reclamation islands C and D from 2006 to 2021. Types of data used in this study is secondary data from Environmental Impact Analysis (ANDAL) documents and reports on the implementation of the Environmental Management Plan and Environmental Monitoring Plan for Reclamation and Development on Islands C and D. Concentrations of turbidity, TSS, BOD, phosphate, and nitrate in coastal waters North of Jakarta around the reclamation islands C and D are fluctuation and several sampling times exceed the quality standard. The species diversity index (H') of phytoplankton in the coastal waters of North Jakarta around the reclamation islands C and D is dominantly included in the criteria for community stability in stable conditions (H 3). Based on the partial correlation test, phosphate with the diversity of phytoplankton species in the waters of the North Coast of Jakarta around reclamation island C and D had a significant relationship (P 0.05).